Salon to Biennial - Exhibitions that made art history : Volume I: 1863-1959 - Altshuler, Bruce (London : Phaidon, 2008)
Salon des Refusés, Paris, 1863 -- The first Impressionist Exhibition, Paris, 1874 -- The first Salon des Indépendants, Paris, 1884 -- Salon d'Automne, Paris, 1905 -- The first Brücke Exhibition, Desden-Löbtau, 1906 -- Manet and the Post-Impressionists, London, 1910 -- The first Blaue Reiter Exhibition, Munich, 1911 -- Les Peintres Futuristes Italiens, Paris, 1912 -- Salon de la Section d'Or, Paris, 1912 -- The first German Autumn Salon, Berlin, 1913 -- The Armony Show, New York, 1913 -- 0.10: The last Futurist Exhibition of Pictures, Petrograd, 1915 -- The first International Dada Fair, Berlin, 1920 -- The first Russian Art Exhibition. Berlin, 1922 -- Film und Foto, Stuttgart, 1929 -- Cubism and abstract art, New York, 1936 -- Degenerate Art, Munich, 1937 -- Exposition Internationale du Surréalisme, Paris, 1938 -- First Papers of Surrealism, New York, 1942 -- Art of This Century, New York, 1951 -- Ninth Street Show, New York, 1951 -- The first Gutai Art Exhibition, Tokyo, 1955 -- The is Tomorrow, London, 1956 -- The New American Painting, New York, 1959.
boek